2005
DOI: 10.1179/136485905x65107
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the direct agglutination test in the early detection of subclinicalLeishmania donovaniinfection: a community-based study

Abstract: The value of a direct agglutination test (DAT) in the detection of subclinical infections with Leishmania donovani has recently been investigated in the Indian state of Bihar, after the sensitivity and specificity of the test had been determined. When used to screen sera from 108 parasitologically confirmed cases of visceral leishmaniasis, 50 patients with active, non-leishmanial infection, and 641 healthy controls living close to, or distant from, an endemic area, the test was found to be 91.7% sensitive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
17
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 18 publications
7
17
0
1
Order By: Relevance
“…In the observed seroconverters who remained asymptomatic, we found that seropositivity did not last into the second year in 86.7%. This is in line with what is reported elsewhere [7], [13], [17]. Six-monthly serological testing might therefore have detected more seroconversions, which would have led to a higher ratio.…”
Section: Discussionsupporting
confidence: 92%
“…In the observed seroconverters who remained asymptomatic, we found that seropositivity did not last into the second year in 86.7%. This is in line with what is reported elsewhere [7], [13], [17]. Six-monthly serological testing might therefore have detected more seroconversions, which would have led to a higher ratio.…”
Section: Discussionsupporting
confidence: 92%
“…The test showed very high sensitivity and specificity for human sera, similar to previous reports (20)(21)(22)(23). Positive and negative predictive values of 100% were obtained at a cut-off titer of 1:800.…”
Section: Discussionsupporting
confidence: 69%
“…A 96-hour, stationary-phase culture of promastigotes of a laboratory-adapted reference strain of L. donovani (WHOM/IN/80DD8) was grown in monophasic medium containing 20% fetal calf serum and used to prepare DAT antigen. 13,14 For sub-clinical infections, the DAT has a sensitivity of 91.7% and a specificity of 100%.…”
Section: Methodsmentioning
confidence: 99%